MicroRNA inhibition using antimiRs in acute human brain tissue sections. Issue 8 (20th June 2022) - Morris, Gareth; Langa, Elena; Fearon, Conor; Conboy, Karen; Lau E‐How, Kelvin; Sanz‐Rodriguez, Amaya; O'Brien, Donncha F.; Sweeney, Kieron; Lacey, Austin; Delanty, Norman; Beausang, Alan; Brett, Francesca M.; et al.
Abstract: Antisense inhibition of microRNAs is an emerging preclinical approach to pharmacoresistant epilepsy. A leading candidate is an "antimiR" targeting microRNA‐134 (ant‐134), but testing to date has used rodent models. Here, we develop an antimiR testing platform in human brain tissue sections. Brain specimens were obtained from patients undergoing resective surgery to treat pharmacoresistant epilepsy. Neocortical specimens were submerged in modified artificial cerebrospinal fluid (ACSF) and dissected for clinical neuropathological examination, and unused material was transferred for sectioning. Individual sections were incubated in oxygenated ACSF, containing either ant‐134 or a nontargeting control antimiR, for 24 h at room temperature. RNA integrity was assessed using BioAnalyzer processing, and individual miRNA levels were measured using quantitative reverse transcriptase polymerase chain reaction. Specimens transported in ACSF could be used for neuropathological diagnosis and had good RNA integrity. Ant‐134 mediated a dose‐dependent knockdown of miR‐134, with approximately 75% reduction of miR‐134 at 1 μmol L −1 and 90% reduction at 3 μmol L −1 . These doses did not have off‐target effects on expression of a selection of three other miRNAs. This is the first demonstration of ant‐134 effects in live human brain tissues. The findings lend further support to the preclinical development of a therapy that targets miR‐134 and offer a flexible platform for the preclinical testing of antimiRs, and other antisense oligonucleotide therapeutics, in human brain.